2001
DOI: 10.1006/jmbi.2001.4675
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations of calcium binding and its role in activity and activation of outer membrane phospholipase A from Escherichia coli

Abstract: Outer membrane phospholipase A (OMPLA) is an integral membrane enzyme that catalyses the hydrolysis of phospholipids. Enzymatic activity is regulated by reversible dimerisation and calcium-binding. We have investigated the role of calcium by X-ray crystallography. In monomeric OMPLA, one calcium ion binds between two external loops (L3L4 site) at 10 A Ê from the active site. After dimerisation, a new calcium-binding site (catalytic site) is formed at the dimer interface in the active site of each molecule at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…Although the crystal structures of many E. coli outer membrane proteins are known (e.g., OmpF [7], LamB [37], OmpA [31], FepA [5], FhuA [11,23], phospholipase A2 [41], OmpT [43], and TolC [18]), the nature and extent of conformational motion within these proteins in vivo is unknown. FepAK332 resides in an unsolved region of L4 (5); K483 resides in L7, and only the ␣ and ␤ carbons of its side chain were crystallographically described, presumably because of the flexibility of the loop (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the crystal structures of many E. coli outer membrane proteins are known (e.g., OmpF [7], LamB [37], OmpA [31], FepA [5], FhuA [11,23], phospholipase A2 [41], OmpT [43], and TolC [18]), the nature and extent of conformational motion within these proteins in vivo is unknown. FepAK332 resides in an unsolved region of L4 (5); K483 resides in L7, and only the ␣ and ␤ carbons of its side chain were crystallographically described, presumably because of the flexibility of the loop (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of OMPLA amino acid sequences in these bacteria also revealed that 30 amino acid residues are completely conserved, indicating an important physiological role of this enzyme in Gram-negative bacteria (Brok et al, 1998). However, in a following study which involved sequence alignment of complete OMPLA sequences in 16 different species of Gram-negative bacteria, Snijder et al (2001) indicated that only 20 amino acid residues are absolutely conserved and another 17 are similar in the sequences of E. coli, Bordetella pertussis, Campylobacter coli, C. jejuni, Enterobacter agglomerans, H. pylori 2669551, H. pylori J99, Salmonella typhi, S. typhimurium, K. pneumoniae, N. gonorrhoeae, N. meningitidis, Pasteurella multocida, Proteus vulgaris, Y. pestis and Y. pseudotuberculosis, therefore yielding a homology of only 13?5 % (Fig. 4).…”
Section: Classification Of Phospholipasesmentioning
confidence: 94%
“…Several of the conserved residues are close in sequence, and form a complete and highly specific consensus sequence motif (YTQ-X n -G-X 2 -H-X-SNG), which proves to be much more specific than a motif based on the active-site residues alone as indicated in Fig. 4 (Snijder et al, 2001). …”
Section: Classification Of Phospholipasesmentioning
confidence: 95%
See 2 more Smart Citations